Beyond splicing: serine–arginine proteins as emerging multifaceted regulators of RNA metabolism in malaria parasites. (December 2022) - Goyal, Manish; Simantov, Karina; Dzikowski, Ron
Abstract : The serine–arginine-rich (SR) proteins play an exceptionally important role in eukaryotic gene expression, primarily by regulating constitutive and alternative splicing events. In addition to their primary role as splicing factors, SR proteins have emerged as multifunctional RNA-binding proteins that act as key regulators of almost every step of RNA metabolism. As in higher eukaryotes, Plasmodium parasites encode several SR proteins, which were implicated in pre-mRNA splicing. However, only a few have been characterized and their biological roles remain understudied. Intriguingly, in addition to splicing regulation, unexpected functions of particular SR proteins have been reported in Plasmodium in recent years. Here, we highlight the key characteristics and different noncanonical splicing functions of SR proteins and discuss potential mechanisms, which might be involved in their multifaceted functionality in Plasmodium .